ST Segment Depression in 12 lead ECG and Severity of Coronary Artery Disease in Non-ST segment elevation Acute Coronary Syndrome (Cardiovascular Journal, 2017)
Background: Patients of non-ST segment elevation acute coronary syndrome (NSTE ACS) is a large group who gets admitted in coronary care units. 12-lead electrocardiogram (ECG) provides the simple available and earliest objective information for risk stratification of NSTEACS. We tried to find out the association between magnitude of ST segment depression and angiographic severity in NSTE ACS patients.Methods: This cross sectional study was carried out in patients with NSTE ACS patients admitted into and underwent coronary angiography. A total number of 105 consecutive patients were included in this study. ST segment depression was measured and categorized according to magnitude of ST segment depression into three groups as Group I: No (